ก๊าซชีวภาพ แหล่งพลังงานทดแทน (Biogas is a Renewable Energy) - ศิริอนุสรณ์ศักดิ์, วิภาดา; จุฬาลักษณานุกูล, สุภางค์; จุฬาลักษณานุกูล, วรวุฒิ (Science Essence Journal, 2011)
ก๊าซชีวภาพเป็นพลังงานทดแทนประเภทหนึ่งที่เกิดจากการย่อยสลายสารอินทรีย์ต่างๆ โดยเชื้อจุลินทรีย์ด้วยกระบวนการย่อยสลายแบบไร้ออกซิเจน องค์ประกอบหลักของก๊าซชีวภาพคือก๊าซมีเทนที่ความเข้มข้นประมาณ 60 เปอร์เซ็นต์โดยปริมาตร วัตถุดิบหลักส่วนใหญ่ในการผลิตก๊าซชีวภาพ คือ น้ำเสีย สิ่งปฏิกูล ของเสียทางการเกษตร และขยะอินทรีย์ กระบวนการผลิตก๊าซชีวภาพประกอบด้วย 4 ขั้นตอน คือ กระบวนการไฮโดรลิซิส เป็นขั้นตอนที่สารอินทรีย์โมเลกุลใหญ่ถูกย่อยสลายกลายเป็นสารอินทรีย์โมเลกุลเล็กลง กระบวนการต่อมาคือ กระบวนการการสร้างกรดจากสารอินทรีย์โมเลกุลเล็กกลายเป็นกรดอินทรีย์ชนิดโมเลกุลเล็ก กระบวนการที่ 3 คือ กระบวนการผลิตกรดอะซิติค และสุดท้ายคือกระบวนการสร้างมีเทน การผลิตก๊าซชีวภาพมีประโยชน์ทั้งในด้านการอนุรักษ์พลังงาน การอนุรักษ์สิ่งแวดล้อม และการนำไปใช้ในการผลิตพลังงานร่วมระหว่างพลังงานกลและไฟฟ้า จากเครื่องกำเนิดเครื่องกำเนิดความร้อนและไฟฟ้าในตัวเดียวกัน ผลิตภัณฑ์ที่เกิดขึ้นสามารถนำไปใช้เป็นวัตถุดิบในอุตสาหกรรมเคมีได้ โดยเป็นสารตั้งต้นเพื่อการผลิตเคมีภัณฑ์ต่าง ๆ การผลิตก๊าซชีวภาพจัดเป็นกระบวนการหนึ่งที่สามารถเพิ่มมูลค่าจากวัตถุดิบมูลค่าต่ำหรือวัสดุเหลือทิ้งจึงนับเป็นกระบวนการลดมลพิษสิ่งแวดล้อม ส่วนก๊าซมีเทนที่ผลิตได้สามารถนำมาใช้เป็นพลังงานทดแทนพลังงานที่ได้จากปิโตรเลียม ก๊าซชีวภาพจึงนับเป็นพลังงานทางเลือกหนึ่งที่สามารถสร้างความมั่นคงทางด้านพลังงานและการพัฒนาพลังงานที่ยั่งยืนในประเทศ Biogas, the clean renewable energy generated from various organic substances under anaerobic conditions by mixed population of microorganisms. The most important biogas component is methane which composed of approximately 60% by volume of methane. Biogas production has usually produced from wastewater, sludge, agricultural waste, and organic waste. There are 4 steps of biogas production. The first step, hydrolysis which large organic molecules are hydrolyzed to small compositions. The second step, acidogenesis is the process that small organic substances are changed to be small organic acid. The third step, acetogenesis which acetic acid is produced and the last step is methanogenesis which methane is produced. The benefit of biogas is of energy conservation, environmental conservation and electrical cogeneration. The produced biogas may be utilized for combined heat and power (CHP) production. Also it can be used as raw material in industrial product and as a precursor for various chemicals production. Biogas production is classified as a process that can add value added to many wastes. Also help to convert some air pollutants that emit to the atmosphere to become a renewable energy instead of petroleum fuel. As well as to become an interesting alternative energy which base on regarding to the security of energy and for sustainable energy development.